Understanding gene interactions controlling resistance to pepper yellow leaf curl disease through phenotype-based analysis - Tri Wahono Dyah Ayu Sayekti; Muhamad Syukur; Sri Hendrastuti Hidayat; Sobir Sobir; Awang Maharijaya (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Pepper yellow leaf curl disease (PYLCD) is the primary disease that affects chili plants, resulting in a loss of quality and quantity. The identification of chili plants resistant to PYLCD is a solution to support optimal chili cultivation. The purpose of this study was to estimate genetic parameters to obtain information on the genetic control of chili resistance to PYLCD. The genotypes used in this study consisted of four parental, four hybrid genotypes, and 180 individuals of the F2 population. The results showed that the genotypes